Evaluation of Education and Its Influence on Satisfaction and Learning Motivation: A Case Study at PPI Muharrikun Najaah Islamic Boarding School - Abdul Latif (Makkah: Journal Of Islamic Studies, 2025)
This study examines the effect of educational evaluation practices on the satisfaction and learning motivation of 10th grade students at the PPI Muharrikun Najaah Islamic Boarding School in Klaten. Using a qualitative case study approach, data was collected through in-depth interviews with teachers and students, participatory observation, and assessment documents. Thematic analysis shows that transparent, participatory, and process-oriented evaluation increases students' sense of appreciation, responsibility, and intrinsic motivation. Student participation in assessment, the quality of feedback, and the suitability of evaluation methods with Islamic boarding school values are key factors. The implications of this study include recommendations for a more dialogical and sustainable evaluation design to improve the quality of learning in Islamic boarding schools.